The opening of the Great Exhibition in Hyde Park, May 1st 1851 - Selous, Henry Courtney (Adam Matthew Digital, 2007)
Electronic image of the original painting (oil on canvas, 210 x 283 cm.) in the Victoria and Albert Museum. The painting shows the Archbishop of Canterbury blessing the Exhibition at the opening ceremony at Crystal Palace. Commissioners, ministers and dignitaries surround the Royal Family. Sir Henry Cole, later the first director of the Victoria and Albert Museum, is included in the group on the left